Visualization of Protein Coding, Long Noncoding, and Nuclear RNAs by Fluorescence in Situ Hybridization in Sections of Shoot Apical Meristems and Developing Flowers. Issue 1 (13th November 2019) - Yang, Weibing; Schuster, Christoph; Prunet, Nathanaël; Dong, Qingkun; Landrein, Benoit; Wightman, Raymond; Meyerowitz, Elliot M.
Abstract : RNA fluorescence in situ hybridization on sections can be used to investigate the tissue/subcellular localization of coding and noncoding RNAs, or for double labeling RNAs, or RNAs and proteins. Abstract: In addition to transcriptional regulation, gene expression is further modulated through mRNA spatiotemporal distribution, by RNA movement between cells, and by RNA localization within cells. Here, we have adapted RNA fluorescence in situ hybridization (FISH) to explore RNA localization in Arabidopsis ( Arabidopsis thaliana ). We show that RNA FISH on sectioned material can be applied to investigate the tissue and subcellular localization of meristem and flower development genes, cell cycle transcripts, and plant long noncoding RNAs. We also developed double RNA FISH to dissect the coexpression of different mRNAs at the shoot apex and nuclear-cytoplasmic separation of cell cycle gene transcripts in dividing cells. By coupling RNA FISH with fluorescence immunocytochemistry, we further demonstrate that a gene's mRNA and protein may be simultaneously detected, for example revealing uniform distribution of PIN-FORMED1 ( PIN1 ) mRNA and polar localization of PIN1 protein in the same cells. Therefore, our method enables the visualization of gene expression at both transcriptional and translational levels with subcellular spatial resolution, opening up the possibility of systematically tracking the dynamics of RNA molecules and their cognate proteins in plant cells.